1980
DOI: 10.4269/ajtmh.1980.29.1205
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Man with Trichuris Vulpis, the Whipworm of Dogs

Abstract: A gravid female Trichuris was found in histopathologic sections of an appendix in a post-mortem examination, and a posterior extremity of a male Trichuris was recovered from the unsectioned portion of the same appendix. These parasites were identified as T. vulpis, the whipworm of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Larger-than-standard T. trichiura eggs have been reported to co-exist with normal-sized eggs, sometimes in the same worm (Yoshikawa et al, 1989). Others dispute the common occurrence of oversized T. trichiura eggs (Kenney and Yermakov, 1980). It has also been reported that T. trichiura eggs of abnormal size and shape can be found following the administration of anthelminthic drugs (Wagner and Chavarria, 1974).…”
Section: Discussionmentioning
confidence: 96%
“…Larger-than-standard T. trichiura eggs have been reported to co-exist with normal-sized eggs, sometimes in the same worm (Yoshikawa et al, 1989). Others dispute the common occurrence of oversized T. trichiura eggs (Kenney and Yermakov, 1980). It has also been reported that T. trichiura eggs of abnormal size and shape can be found following the administration of anthelminthic drugs (Wagner and Chavarria, 1974).…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, the parasite was absent in the previous studies in South Africa 16,17 but reported in stray dogs in neighbouring Zimbabwe 1 8 . Human infections by T. vulpis have been reported 9,12,25 and have been attributed to humans being in continuous contact with environments contaminated by infected dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, another presumed diagnosis was made on the basis of large eggs and on the morphology of nematodes (i.e. a gravid female and a partial adult male) histopathologically found in an appendix during a necropsy of a cancer patient in the USA [19]. The male nematode found in the appendix lacked caudal papillae and had a long cloaca, considered key features in distinguishing T. vulpis from other species of the genus [19,20].…”
Section: Zoonotic or Not Zoonotic This Is The Questionmentioning
confidence: 99%
“…a gravid female and a partial adult male) histopathologically found in an appendix during a necropsy of a cancer patient in the USA [19]. The male nematode found in the appendix lacked caudal papillae and had a long cloaca, considered key features in distinguishing T. vulpis from other species of the genus [19,20]. However, no examination of female characters was performed and, moreover, the authors stated that no "further examination of the posterior male portion" was made, even though they identified the parasites to be T. vulpis [19].…”
Section: Zoonotic or Not Zoonotic This Is The Questionmentioning
confidence: 99%